Cardiovascular health in nursing and medical students - Mateus Goulart Alves; Juliana da Silva Garcia Nascimento; Rafaela Rosário; André Vilela Komatsu; Maria Célia Barcelos Dalri; Jorge Luiz da Silva (Revista Gaúcha de Enfermagem, 2023)
ABSTRACT Objective: To verify whether nursing and medical students take measures regarding their cardiovascular health and the associated risk factors. Method: Cross-sectional study, online data collection with 413 students in February and March 2021, using specific and validated instruments. Kruskal-Wallis, chi-square and logistic regression were adopted for statistical analyses. Results: 73.3% self-reported that they were healthy. We identified a higher risk for developing cardiovascular diseases in sedentary students (OR = 38.6, p < 0.001), with irregular adherence to physical activity (OR = 16.2, p < 0.001) and with a higher level of perceived stress (OR = 1.12, p < 0.001). Conclusion: Students who take action to promote cardiovascular health showed lower risk compared to those who did not. If students do not value their own health during the education process, this may interfere with their professional performance after graduation.